The Role of Mucin in the Toxicological Impact of Polystyrene Nanoparticles - Tajber, Lidia; Santos-Martinez, Maria; Inkielewicz-Stepniak, Iwona; Behan, Gavin; Zhang, Hongzhou; Radomski, Marek W.; Medina, Carla (My University, 2018)
The development of novel oral drug delivery systems is an expanding area of research and both new approaches for improving their efficacy and the investigation of their potential toxicological effect are crucial and should be performed in parallel. Polystyrene nanoparticles (NPs) have been used for the production of diagnostic and therapeutic nanosystems, are widely used in food packaging, and have also served as models for investigating NPs interactions with biological systems. The mucous gel layer that covers the epithelium of the gastrointestinal system is a complex barrier-exchange system that it is mainly constituted by mucin and it constitutes the first physical barrier encountered after ingestion. In this study, we aimed to investigate the effect of polystyrene NPs on mucin and its potential role during NP–cell interactions. For this purpose, we evaluated the interaction of polystyrene NPs with mucin in dispersion by dynamic light scattering and with a deposited layer of mucin using a quartz crystal microbalance with dissipation technology. Next, we measured cell viability and the apoptotic state of three enterocyte-like cell lines that differ in their ability to produce mucin, after their exposure to the NPs. Positive charged NPs showed the ability to strongly interact and aggregate mucin in our model. Positive NPs affected cell viability and induced apoptosis in all cell lines independently of their ability of produce mucin.
PUBLISHED
Keywords: Polysytrene; Nanoparticles; Mucin; DLS; QCM-D; Cytotoxicity; Immunology, Inflammation & Infection; Nanoscience & Materials; NANOPARTICLES